The Literary Benefits of Linguistic and Cultural Hybridity - Radojkovich, Leanne (Auckland University of Technology, 2010)
The objective of this exegesis is to show how linguistic and cultural hybridity create a unique prose style, and how my stories sit within that style. I will use Grace Paley and Lucia Berlin to demonstrate the distinctive narrative techniques. These include the use of sensuous details (instead of descriptions) to make place and character palpable; dialogue that convincingly evokes living speech; plots which emanate from the characters, rather than the other way round; and open-ended resolutions, as in real life. I will then show how I use these narrative techniques in my collection Happiness and other stories.
Keywords: Literary fiction; Cultural hybridity; Linguistic hybridity; Mixed identities; Prose style; Narrative techniques